Are there common assembly rules for different grasslands? Comparisons of long‐term data from a subtropical grassland with temperate grasslands. (8th July 2020) - Ward, David; Kirkman, Kevin P.; Tsvuura, Zivanai; Morris, Craig; Fynn, Richard W. S.
Abstract: Questions: How consistent are assembly rules for grassland communities from different regions in response to management? We compared vegetation response using long‐term experiments in subtropical South Africa with published temperate Park Grass (UK) and Konza Prairie (USA) results. Location: Ukulinga, Pietermaritzburg, South Africa. Methods: Long‐term experiments in the South African site included a fertilizer experiment (VFE) that was compared with Park Grass and a burning and mowing experiment (BME) that was compared with Konza Prairie. Results: We found consistent vegetation patterns of this subtropical grassland and the temperate grasslands at Park Grass and Konza Prairie. In the comparison of the burning and mowing experiments, species richness in the BME at Ukulinga declined across mowing treatments but did not change between control and intermediate burns as found at Konza Prairie. There was dominance by a few species in the subtropical grassland and the two temperate grasslands under high productivity and frequent burns. Annual burns resulted in lower species richness at both subtropical Ukulinga and temperate Konza Prairie. At both temperate Park Grass and Ukulinga, few species dominated in highly fertilized plots, both sites showed a negative effect of nitrogen amount, and there was a positive effect of lime on species richness. Conclusions: Consistent results from long‐term series of subtropical and temperate grasslands suggest that there are similar community assembly rules regardless of different climatic conditions and different species pools. A possible underlying mechanism for community assembly at Ukulinga and Konza Prairie for both fertilization, burning and mowing may be shade tolerance. At Ukulinga and Park Grass, changes in species richness (negative effects of increasing nitrogen amount and positive effects of lime) were remarkably similar. Most of the common grass species in South Africa showed evidence of competition, supporting niche‐based assembly rules. Abstract : We compared vegetation responses using long‐term fertilizer and burning and mowing experiments at Ukulinga (subtropical South Africa) with published temperate Park Grass (UK) and Konza Prairie (USA) results. Consistent results from long‐term series of subtropical and temperate grasslands suggest that there are similar community assembly rules regardless of different climatic conditions and different species pools, probably mediated by shade tolerance.